Acquired Concurrent EGFR T790M and Driver Gene Resistance From EGFR-TKIs Hampered Osimertinib Efficacy in Advanced Lung Adenocarcinoma: Case Reports - Zeng, Yue; Feng, Yuanqing; Fu, Guihua; Jiang, Junlan; Liu, Xiaohan; Pan, Yue; Hu, Chunhong; Liu, Xianling; Wu, Fang (Frontiers in Pharmacology, 2022)
The acquired resistance of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) is inevitable and heterogeneous. The strategies to overcome acquired resistance are significant. For patients with secondary T790M-positive after early generation EGFR-TKIs, osimertinib is the standard second-line therapy. In patients resistant to prior early generation EGFR-TKIs, the acquired T790M mutation overlaps with other driver gene resistance, such as HER2-and MET amplification, accounting for 4–8%. The efficacy of osimertinib is unclear in patients with concurrent multiple driver gene resistance. We here report a patient who acquired EGFR T790M, STRN-ALK fusion, and EGFR amplification after gefitinib progression and subsequent MET amplification acquired from osimertinib. The other patient acquired EGFR T790M and MET amplification post-dacomitinib and acquired CCDC6-RET fusion after osimertinib treatment. Besides, subsequent new bypass activations were the possible resistance mechanisms to second-line osimertinib. Both patients had progression-free survival (PFS) less than 4 months and limited benefits from osimertinib second-line therapy. The T790M accompanying driver gene resistance will be a new subtype after EGFR-TKIs progression, needing effective treatment options.